Evaluation of the Nutritive Value of Mediterranean Roughages - Tisserand J.-L. (Evaluation of the Nutritive Value of Mediterranean Roughages, 1999)
This research, funded by a European Union contract, was carried out by seven laboratories from six European countries, whose objective was to improve knowledge of the nutritive value of forages and by-products of the Mediterranean region. The work has focused on: (i) Feeding behaviour of animals, to gain knowledge on bite numbers on rangelands. (ii) Chemical and biological methods. (iii) The specific problem of polyphenolics. The possibilities and conditions for using the main methods available were evaluated. Of these methods, the gas test method seems to be the most promising, being simple to use, reproducible and allowing the prediction of level of intake and apparent digestibility of forages, as well as assessing the impact of phenolic compounds. The level of intake and digestibility measured in vivo on small ruminants were taken as a reference to test the reliability of in vitro and in situ methods used for assessment under inexpensive conditions. The implementation of chains of analyses involving the seven teams in the project and four laboratories from Algeria, Morocco and Tunisia allows the feasibility and reproducibility of the selected methods to be determined.